Staging holiness: the case of Hospitaller Rhodes (ca. 1309-1522) - Zoitou, Sofia (Mediterranean art histories, 2021)
The Hospitallers' institutions -- The Borgo and the area outside the walls -- Our Lady of Phileremos.